The ‘Homeless Families with Children’ litigation: a case study of court enforcement of socio-economic rights - Clary, R (Foundation for Law, Justice and Society, 2008)
In the United States, courts have played a key role in defining socio-economic rights and in enforcing the government's obligations to provide and protect those rights. Such long-term judicial oversight has provoked political debate over the proper role of the courts versus the executive branch. That debate has five key aspects: (1) declaring the right at issue, including the source of that right; (2) defining the scope of the right; (3) enforcing the right; (4) the (alleged) downsides of long-term judicial oversight; and (5) defining when the court should end its role. This policy brief uses the Homeless Families with Children litigation (McCain v. Bloomberg) as a case study.